(untitled) (Sains Humanika, 2011)
Legislation is considered as important element for school organization with the assumption that school operations involved law element. This study was conducted to investigate the primary school administrators’ knowledge about the legislation in education. In addition, this study also identified differences significant of demographic factors, school administrators, legal knowledge, which involves schools and the relationship between demographic factors with knowledge of the legalization. Sample for this study were 87 primary school administrators of 20 schools which were school’s headmasters, Senior Assistant (Administration), Senior Assistant (Student Affairs); Senior Assistant (Co-curriculum) and Senior Assistant (Evening Session). Data were analyzed using descriptive and inferential statistics such as frequencies, percentages and mean scores, t-test, one-way ANOVA. Results showed that headmaster have high level of knowledge related the produces, regulation and law in education. In addition, primary school administrators frequently used educational law and legislation as their main source while leading and managing the school. However, school administrators also admitted they were less exposed to courses and workshop related to education legislation. Suggestions were also forwarded to enhance the primary school capabilities related to legislation in education.